SEASONAL DYNAMICS OF NEMATODES OF CUCUMBER HARVEST (FOR EXAMPLE, THE OLTIARYK DISTRICT) (Scientific journal of the Fergana State University, 2024)
The article presents information about the composition of the fauna of nematodes, their environmental characteristics and trophic relationships with plants during the growing season of cucumber crops grown in the farms of the Altyarik district of the Ferghana region. As a result of studies of the species composition and quantitative dynamics of nematodes of cucumber crops, 58 species (1790) of the phonematode belonging to 2 subclasses, 9 births, 21 family and 33 kinds were revealed. The maximum number of species was observed during the germination of the vegetation of the cucumber, and the smallest - during the growing season of plants.